The debate between a man and his soul : a masterpiece of ancient Egyptian literature - Allen, James P., 1945- (Culture and history of the ancient Near East ;, 2011)
This book is a new study of one of the masterpieces of ancient Egyptian literature, offering new readings and translations, along with an analysis of the text's grammar and versification, and a complete philological apparatus.